Application of extracorporeal membrane oxygenation in the remote transport of a patient with a ruptured sinus of Valsalva aneurysm: a case report - Liao, Xiaozu; Zhong, Shi; Huang, Weizhao; Li, Binfei (Frontiers in Surgery, 2024)
Background A ruptured sinus of Valsalva aneurysm can lead to rapid heart failure and sudden cardiac death. Management of patients who develop severe heart failure and need to be transferred to a specialized hospital for surgical treatment can be challenging. In patients with severe shock due to a ruptured sinus of Valsalva aneurysm into the right atrium, extracorporeal membrane oxygenation (ECMO) transport is an effective means to ensure patient safety, but increases the right cardiac load. We report the experience of veno-arterial (VA) ECMO transport in the treatment of acute cardiogenic shock caused by rupture of a congenital sinus of Valsalva aneurysm. Case presentation We describe the case of an 18-year-old male who began having acute episodes of chest pain, shortness of breath, palpitations, and dizziness 18 h before presenting to the emergency department. An echocardiogram revealed an acute ruptured sinus of Valsalva aneurysm and a shunt to the right atrium. The patient presented with severe shock. VA-ECMO was administered to ensure safe transport to the cardiac center. The outcome of emergency surgical repair was good. The patient was on ECMO for 8 h. He returned to the general ward after 7 days and was successfully discharged after 40 days. He had good exercise tolerance 2 years after surgery and no evidence of heart failure. Conclusion Although ECMO transport can increase right cardiac load, it is an effective and safe method to move patients with severe shock caused by a ruptured sinus of Valsalva aneurysm into the right atrium. Methods to decrease right cardiac load, such as decreasing ECMO flow combined with cardiotonic drugs, should be adopted. Successful treatment involves rapid establishment of cardiopulmonary bypass and urgent repair of the ruptured sinus of Valsalva aneurysm.